A CORRELATION BETWEEN THE EIGHT GRADE STUDENTS’ PARTICIPATION IN ENGLISH EXTRACURRICULAR ACTIVITIES AND THEIR SPEAKING ABILITY AT SMPN 6 PEKANBARU - Monalisa Dewa Ayu; Supriusman '; Maisrul ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed at investigating whether there is a correlation between between students’ participation in English Extracurricular at school and their speaking ability at SMPN 6 Pekanbaru. This research used simple random sampling. The researcher found that extracurricular activity can improve students’ speaking ability at school. The result showed that coefficient correlation between two variable is 0,84, which means there is positive correlation between two variables. The researcher suggests the English teachers to pay more attention on the other factor that influencing speaking ability, such as: extracurricular activityKeyword:correlation, ekstracurricular, speaking